2024
DOI: 10.3847/1538-4357/ad072f
|View full text |Cite
|
Sign up to set email alerts
|

How Can the Optical Variation Properties of Active Galactic Nuclei Be Unbiasedly Measured?

Xu-Fan Hu,
Zhen-Yi Cai,
Jun-Xian Wang

Abstract: The variability of active galactic nuclei (AGNs) is ubiquitous, but has not yet been understood. Measuring the optical variation properties of AGNs, such as the variation timescale and amplitude, and then correlating them with their fundamental physical parameters has long served as a critical way of exploring the origin of AGN variability and the associated physics of the accretion process in AGNs. Obtaining accurate variation properties of AGNs is thus essential. It has been found that the damped random walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…As we mentioned in Section 1, the requirement for recovering the intrinsic damping timescale is that the intrinsic damping timescale (rather than the best-fitting one) should be <10% (or 20%) of the baseline. The results of Hu et al (2024) show that if the intrinsic τ DRW is 10% of the baseline, although the statistical expectation of the output best-fitting τ DRW is the same as the intrinsic τ DRW , its 1σ dispersion is as large as 50%. If one only requires that the best-fitting τ DRW is <10% (or 20%) of the baseline, the statistical expectation of τ DRW can still be significantly biased.…”
Section: Simulation Stepsmentioning
confidence: 98%
See 3 more Smart Citations
“…As we mentioned in Section 1, the requirement for recovering the intrinsic damping timescale is that the intrinsic damping timescale (rather than the best-fitting one) should be <10% (or 20%) of the baseline. The results of Hu et al (2024) show that if the intrinsic τ DRW is 10% of the baseline, although the statistical expectation of the output best-fitting τ DRW is the same as the intrinsic τ DRW , its 1σ dispersion is as large as 50%. If one only requires that the best-fitting τ DRW is <10% (or 20%) of the baseline, the statistical expectation of τ DRW can still be significantly biased.…”
Section: Simulation Stepsmentioning
confidence: 98%
“…We then investigate the dependence of the best-fitting τ DRW on wavelength obtained from the CHAR model and compare them with the results in S22. Previous studies have shown that the best-fitting τ DRW is significantly underestimated if the baseline is not longer than 10 (or five) times the intrinsic damping timescale (Kozłowski 2017;Suberlak et al 2021;Hu et al 2024). S22 selects a subsample with the best-fitting damping timescales <20% of the baseline containing 27 sources.…”
Section: Dependence Of τ Drw On Wavelengthmentioning
confidence: 99%
See 2 more Smart Citations
“…It is often speculated that the damping timescale is closely related to quasar properties (e.g., Kelly et al 2009;Sun et al 2018b). For instance, Burke et al (2021) obtain the relationship between the DRW damping timescale and SMBH mass: Meanwhile, it is stressed that the damping timescale can easily be biased unless the intrinsic t damping is less than 10% of the light-curve duration (e.g., Kozłowski 2017;Hu et al 2024). The synthetic V-band light curve of our target has a long duration of ∼6230 days (observed frame), enabling us to robustly measure the damping timescale since the expected damping timescale in the observed frame is only 109 (1 + z) = 143.7 days (Equation (4); Burke et al 2021).…”
Section: The Damping Timescalementioning
confidence: 99%